Ammonium 4-(4-carboxyphenoxy) benzoate - Li, He-Ping; Ng, S.W. (International Union of Crystallography, 2010)
The anions of the title salt, NH4+center dot HO2CC6H4-O-C6H4CO2, are linked by intermolecular -CO2H center dot center dot center dot O2C-hydrogen bonds, forming a polyanionic chain in the crystal; adjacent chains are connected through the ammonium cation into a layer structure, with the ammonium cation serving as hydrogenbond donor to four carboxylate O atoms. The cation and anion both lie on special positions of 2 site symmetry. In the anion, the rings make a dihedral angle of 65.3 (1)degrees. The acid H atom is disordered about the special position.